A highly efficient, colorimetric and fluorescent probe for recognition of aliphatic primary amines based on a unique cascade chromophore reaction. Issue 66 (30th July 2019) - Li, Lanqing; Li, Wenting; Ran, Xueguang; Wang, Lingyun; Tang, Hao; Cao, Derong
Abstract : A highly efficient, colorimetric and fluorescent probe for recognition of aliphatic primary amines based on a unique cascade chromophore reaction is developed. Abstract : Pyrrolopyrrole aza-BODIPY based nanoaggregates were reported as a highly selective and sensitive probe for recognition of aliphatic primary amines with a novel cascade chromophore reaction. Due to its distinct reaction characteristics, this probe loaded test strip can conveniently detect n -hexylamine vapor and monitor the freshness of shrimp.